Effectiveness of polymeric coated films containing bacteriocin-producer living bacteria for Listeria monocytogenes control under simulated cold chain break. (December 2018) - Degli Esposti, Micaela; Toselli, Maurizio; Sabia, Carla; Messi, Patrizia; de Niederhäusern, Simona; Bondi, Moreno; Iseppi, Ramona
Abstract: Nisin, enterocin 416K1 and living bacteriocin-producer Enterococcus casseliflavus IM 416K1 have been entrapped in polyvinyl alcohol (PVOH) based coatings applied to poly (ethylene terephthalate) (PET) films, and their effectiveness in the control of the growth of Listeria monocytogenes ATCC 19117 has been tested. The anti-listerial activity of the doped coated films was evaluated by both a modified agar diffusion assay and a direct contact with artificially contaminated precooked chicken fillets stored at 4 °C, 22 °C and under simulated cold chain break conditions (1 day at 30 °C). The live- Enterococcus- doped film showed a more remarkable activity than nisin- and enterocin-doped films over long times both at 4 °C and 22 °C. The use of this film at 22 °C resulted in full inactivation of L. monocytogenes from the seventh day of the test. Live- Enterococcus- doped film displayed a much better antilisterial activity in comparison to nisin- and enterocin-doped films also in samples incubated at 4 °C, and submitted at one day (3rd or 7th day) of storage at 30 °C, to simulate cold chain break conditions. All results suggest that the live- Enterococcus -doped film can behave as a smart active food packaging, very effective in cold chain break conditions when the Listeria growth is fast. Highlights: Films coated with bacteriocins or live enterococci are tested against L. monocytogenes. Activity was tried in vitro and on food at 4 °C, 22 °C and in temperature abuse settings. Data confirm the film effectiveness in L. monocytogenes control during food storage. Live- Enterococcus -doped film is very active in simulated cold chain break conditions.